Purification of metallo-B-lactamase CcrA from Bacteroides fragilis with salting-out method - Liu,Cheng-Cheng (2013)
A simple and effective salting-out method was developed for the purification of the metallo-β-lactamase CcrA from Bacteroides fragilis based on the plasmid pMSZ02, in which the crude protein secreted into growth medium was precipitated by 80% sulfate saturation of the medium and purified with Q-Sepharose to offer pure CcrA with yield of 20.1 mg per litter medium. The dependence of the amount of protein precipitation on sulfate saturation was investigated, which showed that more than 80% sulfate saturation resulted the maximum protein precipitated. The purified CcrA was evaluated by steady-state kinetics using penicillin G and cephalothin V as substrates, which showed the Km values of 68±2 and 17±2 µM and Kcat values of 63±1 and 102±3 S-1, respectively. The comparison with the data of the protein from literature method showed that the salting-out method was viable, and it could be useful for the purification of other proteins secreted into growth medium.